Pengaruh Pemberian Insentif terhadap Kinerja Konsultan Pengawas dalam Proyek Konstruksi - Feno Candri; Wahyudi P. Utama; Rini Mulyani (Universitas Batanghari Jambi, 2026)
One measure of the success of a construction project is the achievement of the project completion time target. Time is one of the main targets in a construction project. The parties involved in a construction project are service users and service providers. Supervision consultants are service providers. In an effort to improve the performance of supervision consultants, incentives are often used as an effective strategy, both in financial and non-financial forms, to motivate employees to work harder and focus on results. The purpose of this study is to examine the effect of incentives on the performance of supervisory consultants in the city of Jambi. The research method used is quantitative descriptive. Based on a literature review, there are 21 incentive variables, with factor analysis forming three new factors consisting of valid and reliable variables. The results of the study obtained a constant value (a) of 8.132, which can be interpreted as a direct relationship between the independent and dependent variables. This shows that if all variables, including Incentive Effectiveness (XA), Project Management Efficiency and Responsiveness (XB), Compliance, Sustainability, and Incentive Fairness (XC) are 0% or unchanged, then the value of Project Supervision and Control Effectiveness (YA) is 8.132. The most dominant factor affecting the performance of supervisory consultants is incentive effectiveness. Incentives are given if the project is completed on time, within budget, is of high quality, has minimal errors, is safe, and is able to meet the needs of the owner and maintain communication. Clear incentives have been proven to increase the motivation and performance of consultants.